Pengembangan Strategi Pemasaran Digital dan Branding pada UMKM Aitri Kue - Waladdin Panggabean; Nazwa Maulidya Putri; Daniel Obed Kurniawan; Asifa Raditya; David Simamora; Ratu Prima Rahmadhani; Violita Nova Hadistia; Muhammad Iqbal Rahardian; Angelica Dan Made; Vanessa Ria Balqis; Chlara Chlaudia Anelka (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This community service program aims to strengthen the digital marketing and branding strategies of the Aitri Kue MSME in Margo Mulyo Village, Balikpapan. Despite operating since 2010 and establishing partnerships with companies and hospitals, the management of promotions and visual identity remains suboptimal. The method used was descriptive qualitative, encompassing observation, interviews, planning, implementation, monitoring, and evaluation. The program focused on updating the visual identity, developing promotional media, installing standing banners, and creating digital content on social media. The results showed significant improvements in brand consistency, business visibility, and promotional effectiveness. Furthermore, the mentoring program successfully enhanced business owners' understanding of more systematic marketing practices. Overall, the integration of digital marketing and visual branding has been proven to strengthen professionalism and support the sustainability of MSMEs in the digital era.